PENGARUH TINGKAT KESEJAHTERAAN DAN PENGAWASAN TERHADAP SEMANGAT KERJA KARYAWAN PT. RAIH USAHA KARYA MANDIRI PEKANBARU - JULIAN, ELVRY; Wijaya, Errin Yani; ', Marzolina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
The study was conducted at PT. Raih Usaha Karya Mandiri Pekanbaru in order to determine and analyze the influence of the level of welfare and supervision of employee morale PT. Raih Usaha Karya Mandiri Pekanbaru. Employee morale is an important component in determining the progress of the company or organization, there are several reasons why employee morale require attention from management, namely, high morale, making the work assigned to him can be solved with a shorter time, can reduce the rate of absenteeism due lazy, makes employees feel senag work, these three things will minimize the possibility of employees to move work to other places In this study, there are three variables, namely, the level of welfare (X1), supervision (X2), and morale (Y). The study population was 61 people, and the samples taken were all employees of PT. Raih Usaha Karya Mandiri Pekanbaru. Collecting data in this study is done by giving questionnaires to the respondents. In terms of data analysis, this study uses linear regression method SPSS version 18. Results of this study there are significant levels of welfare and supervision of employee morale. Welfare is meant is that it can be viewed as a further aid money to employees. Especially payments to those who are sick, money saving assistance to employees, the division in the form of bonuses, insurance, hospitalization, and pensions. And also there is the influence of supervision on employee morale, supervision required, among others, leadership should be more frequent direct supervision to their employees and work assessment among employees, so that employees are supervised felt to be more active and in good working at PT. Raih Usaha  Karya Mandiri Pekanbaru. Keywords: Morale, welfare, and supervision